2014
DOI: 10.1088/1674-4926/35/12/124001
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of some parameters into the behavior of quantum dot solar cells

Abstract: The main goal of this paper is to determine the accurate values of two parameters namely the surface generation—recombination rate and the average total number of electrons density generated in the i-region. These values will enhance the performance of quantum dot solar cells (QDSCs). In order to determine these values, this paper concentrates on the optical generation lifetime, the recombination lifetime, and the effective density state in QDs. Furthermore, these parameters are studied in relation with the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The intermediate band solar cells (IBSCs) have attracted great attention due to the possibility of exceeding the Shockley-Queisser (SQ) limit [1][2][3][4]. From the analysis by Luque et al [5,6], the IBSC's concept yields a maximum theoretical efficiency of 63.2%, surpassing the limit of 40.7% of single gap solar cells under maximum light concentration (the sun being assumed as a blackbody at 6000 K) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate band solar cells (IBSCs) have attracted great attention due to the possibility of exceeding the Shockley-Queisser (SQ) limit [1][2][3][4]. From the analysis by Luque et al [5,6], the IBSC's concept yields a maximum theoretical efficiency of 63.2%, surpassing the limit of 40.7% of single gap solar cells under maximum light concentration (the sun being assumed as a blackbody at 6000 K) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The IBs allow for the absorption of low-energy photons that would otherwise be transmitted through the bulk SCs [44]. In the last decade, there has been an extensive effort to demonstrate the QDIBSCs with a central focus on III-V compound semiconductors [45][46][47][48][49][50][51][52][53]. QDs must be dense to achieve the sufficient photo-absorption in QD layers.…”
Section: Intermediate Band Solar Cellsmentioning
confidence: 99%
“…The reason for improvement of the efficiency in QDIBSCs is mainly that the IB formed among QDs increases absorption of longer wavelength region sunlight and reduces non-radiative combination. Recent studies have shown that efficiencies of QDIBSCs can be improved by using different compositions from III-V semiconductor materials [48][49][50][51][52][53]. It depends essentially on controlling each of the QDs size and the distances between them in the host materials.…”
Section: Intermediate Band Solar Cellsmentioning
confidence: 99%
“…The direct radiation includes only the radiation from the solar and circumsolar radiation, as seen from the earth's surface. 1 Both the sun and the solar cell emit or absorb radiation with a distribution similar to that of a blackbody, therefore the equation for the flux of photons absorbed at the sun's surface ðf s Þ is [13][14][15] …”
Section: Traditional Solar Cellmentioning
confidence: 99%